Histamine Induces Egr-1 Expression in Human Aortic Endothelial Cells via the H1 Receptor-mediated Protein Kinase Cδ-dependent ERK Activation Pathway - Hao, Feng (American Society for Biochemistry and Molecular Biology, 2008)
Histamine, a potent inflammatory mediator, has multiple effects on the pathogenesis of atherosclerosis. This study investigates the effect of histamine on the expression of early growth response factor 1 (Egr-1), a master transcription factor that regulates the expression of an array of atherogenic genes in atherosclerotic lesions. Histamine markedly and rapidly induces Egr-1 mRNA and protein expression in primary human aortic endothelial cells (HAECs). Histamine-induced Egr-1 expression is dependent on the activation of the H1 receptor. Histamine also rapidly and transiently activates protein kinase C-δ (PKCδ), extracellular signal-regulated kinase (ERK)1/2, p38 kinase, and c-Jun N-terminal kinase (JNK) prior to Egr-1 induction. Using specific pharmacological inhibitors and small interfering RNA technology, we determined that PKCδ and ERK, but not p38 and JNK, mediate histamine-induced Egr-1 expression. Our data provide the first evidence that histamine regulates expression of Egr-1 in mammalian cells and demonstrate a novel role of PKCδ in up-regulation of Egr-1 expression. The present study reveals the following regulatory mechanism: histamine up-regulates Egr-1 expression in primary HAECs via the H1 receptor and the PKCδ-dependent ERK activation pathway. Our data also imply that CREB, a downstream component of the ERK pathway, regulates Egr-1 expression in HAECs. Importantly, these results suggest a central role of Egr-1 in histamine-induced gene expression and in histamine-induced vascular disease.